TEACHING METHODS USED BY LECTURERS IN TEACHING LISTENING IN THE SECOND SEMESTER AT ENGLISH LANGUAGE EDUCATION DEPARTMENT - Hikmatul Fitriyah (La Tansa Mashiro, 2021)
The purpose of this study are to know the appropriate teaching methods used by the lecturers in teaching listening II at an English Language Education Department. This study is conducted due to the reality that students are not interested in listening classes because they face challenging times understanding the audio. This research used descriptive qualitative research. In this case, teaching listening II was investigated by the researcher to explore the teaching methods used by the lecturers. The data of the study were analyzed to report the teaching methods used by the lecturers. The instruments to collect the data were observation, questionnaire, and interview. The result of the analysis of teaching methods showed that the lecturers used different methods in teaching listening II. The methods used by the lecturers are: Direct Method, Audio Lingual Method, Grammar Translation Method, and Task-Based Learning. Those methods are appropriate for teaching listening because there are some characteristics and goals in those methods that make the students interested in listening class.